Flow field characterization between vertical plate electrodes in a bench-scale cell of electrochemical water softening. (24th February 2022) - Chen, Qi; Lin, Wei; Wang, Zhonghao; Yu, Jiuyang; Li, Jimin; Wang, Zhangwei
Abstract: To analyze the effect of flow characteristics on electrochemical water softening, characteristics of flow fields in the vicinity of vertical plate electrodes in a bench-scale electrolysis cell for electrochemical water softening were visualized using particle image velocimetry technology, and the hardness drop values under different process conditions were measured. Properly increasing the current density or reducing the electrode spacing can increase the average flow velocity in the electrode gap. Excessive current density will cause bubble accumulation, form a bubble vortex, interfere with the orderly flow of surrounding liquid and reduce mass transfer efficiency. When the electrode spacing is 120 mm, the highest water softening efficiency measured at the current density of 60 A/m 2 is 16.56%. When the current density is 50 A/m 2, the highest average speed measured at the electrode spacing of 60 mm is 0.00169 m/s, but the highest water softening efficiency measured at the electrode spacing of 90 mm is 23.3%.The circulation efficiency in the electrode gap of a semi-closed structure is lower than that of a free convection structure. The behavior of bubbles is the key to flow and mass transfer. It is important to consider its influence on bubble behavior when optimizing electrochemical parameters. HIGHLIGHTS: Effect of flow characteristics between vertical plate electrodes on water softening efficiency. The main flow patterns of mass transfer between vertical plate electrodes. Effect of bubble behavior on flow patterns between vertical plate electrodes. Optimization of flow mass transfer efficiency by current density, electrode spacing and electrode position. Trend of velocity distribution between vertical plate electrodes.